DAMPAK KEBERHASILAN PEMERINTAH VIETNAM DALAM MENEKAN KASUS COVID-19 PADA KESTABILAN DAN KESEHATAN NEGARA - Dwi Endah Pratiwi; Restu Nissa Hafiza (FISIP Universitas Tanjungpura, 2022)
Vietnam is the best country to deal with this pandemic. Even on one occasion, WHO Director General, Tedros Adhanom Ghebreyesus had asked countries with high numbers of Covid-19 sufferers to follow Vietnam's example. According to WHO, the Vietnamese government's rapid response is the key to overcoming the emergency in controlling the crisis at an early stage. If you look at the geographical location of Vietnam which is quite close to China as the initial location of the emergence of this virus, it is not impossible that Vietnam is one of the countries that is very vulnerable to the spread of the virus. But Vietnam can go through that and become the 20 safest countries from Covid-19. Even Vietnam has rebuilt its country. What is the focus of the Vietnamese state in suppressing Covid-19, apart from its quick response, is how strictly Vietnam filters people coming in and out of the country and from outside the country. This restriction also includes minor policies in it such as massive inspection, visa suspension, etc. Vietnam has also learned a lot from its past infectious disease experience, so it has prepared an initial investment in the health sector. Policies in the form of strict restrictions on entry and exit as well as awareness to learn from this experience can be applied and help Indonesia suppress Covid-19 cases in Indonesia.